Hysteresis Compensation Application in Magnetostrictive Inkjet Print-head - Bao, Tran Quoc (Engineering, Technology & Applied Science Research, 2025)
This study presents the experimental hysteresis compensation method implemented in a magnetostrictive inkjet print-head, utilizing the Terfenol-D, a giant magnetostrictive material. The distinctive features between the input energy and the output displacement are known as the inherent hysteresis characteristics in a ferromagnetic material, which cause major obstacles to the output performance. Therefore, an appropriate compensation method is necessary to reduce the Hysteresis Loss (HL). Previous research has focused on mathematical models such as the Preisach or the Jile – Atherton models. However, such models are complicated, and it is thus challenging for them to control hysteresis in a real-time system. This paper solves the aforementioned problem based on the charging and discharging of an RC-circuit, which is known as the experimental compensation method. In the experiment, an attempt to compensate for hysteresis at the frequencies of 5 Hz and 100 Hz is made. For each frequency, different ranges of the capacitance value are selected to find the resistance value. A resistor with the value of 50 Ω is chosen and integrated into the compensation circuit. Through the experiment, optimal capacitance values of 335 μF and 10.75 μF are obtained at the considered frequencies. The results are attained using PEDOT: PSS and silver nanoparticle ink to validate the droplet formation. In both cases, the droplet formation is estimated and calculated in terms of the droplet diameter, tail length, droplet volume, and breaking time.